Estimation of Two Bioactive Compounds From Azadiracta Indica A. Juss. Leaves Using HPLC - WILLY SHAH; NILAN RANE; M.B.KEKARE; VIKAS VAIDYA (International Journal of Pharma and Bio Sciences, 2010)
Sensitive, simple, and accurate high-performance liquid chromatographic method has been established for determination of rutin and quercetin both simultaneously in Azadiracta indica A.Juss. leaf powder. The chromatographic separation was performed on Phenomenex C18 column (250 x 4.6, 5 μm) with a 60:40 v/v mixture of methanol and 0.1% O-phosphoric acid in water at the flow rate of 1.2 mL/min and detection at 258 nm, with a run time of 10.0 min. The developed method was then validated using statistical analysis. This will help in qualitative analysis of plant material using fingerprint pattern and quantitative analysis of rutin and quercetin.